Error analysis on abstracts of the students' final writing projects - Gita Rahmi (Mitra Palupi, 2022)
Background: Writing final project is one of the requirements for graduation from the college and abstract is one of the elements that students need to write too. Students' errors in writing abstracts need to be analyzed. Purpose: This research was conducted to find out errors made by the students. Design and Methods: In this qualitative research, the data were collected from students' abstracts of their final writings. There were six abstracts from six students collected and investigated. The data were analyzed by using theory from Dulay, Burt and Krashen (1982). The errors were classified as omission, addition, misformation and misordering. Results: Based on the research, it was found that the students had 34 errors in their abstracts. The students made 10 errors of omission, 2 errors of addition, 20 errors of misformation and 2 errors for misordering. The result of this research is expected to help the lecturers find out the solutions to overcome the errors in students’ writing. For the students themselves, it is expected that the research shows them the common errors and difficulties in academic writing, especially abstract.